Features extraction of geometry defect monitoring in cylindrical piping - Mokhtar, Mohd Faiz (2013)
This study aims to investigate the features of wave in the single Polyvinyl Chloride (PVC) cylindrical pipeline. This project involved the monitoring process of without defect and defect single pipeline. The experiment process involved the simple geometry defect including the horizontal and vertical cracks. The sensor used in this project is the Piezoelectric Wafer Active Sensor (PWAS) which the sensors use to detect the lamb wave. As a part of non-destructive test process, this crack detection process involving the process of analyzing wave obtained from the sensor. The size of defect is the manipulated variables use in this project which including the size of crack start from 1 cm to 5 cm. However, this project is only concentrate only on the semicircular part of the cross-section of the pipeline. Because of that, all the six sensors used in this project attached only in the distance 36º between each sensor. This project indicates the different pattern of wave for each sensor as each sensor has own angle from the midpoint of the circular cross-section. The different pattern produced by each sensor in the present of crack and for normal pipe was analyzed for the understanding the effect of the defect in the normal single PVC pipeline. The data produced by each sensor then was filter to get the best accurate and consistent data. Filter data next to analyzed followed by the features choice for time domain including the maximum peak, minimum peak, velocity of the wave and maximum amplitude versus angle of the sensors for both horizontal and vertical defect. The results of each features is discussed graphically in results and discussion chapter.